Association between frailty and oral function in rheumatoid arthritis patients: A multi-center, observational study - Yasumori Sobue; Mochihito Suzuki; Yoshifumi Ohashi; Ryo Sato; Yusuke Ohno; Junya Hasegawa; Takaya Sugiura; Kenya Terabe; Shuji Asai; Shiro Imagama (Archives of Rheumatology, 2025)
Objectives: This study aims to investigate the association between frailty and oral function in rheumatoid arthritis (RA) patients and to identify practical markers for early frailty detection and potential intervention strategies. Patients and methods: A multi-center observational cohort study (T-FLAG) included a total of 661 RA patients (186 males, 475 females; mean age: 68.5±13.5 years; range, 18 to 100 years) between June 2023 and August 2023. Frailty was assessed using the Kihon Checklist (KCL) (frailty: score ≥8). Oral function scores were based on Question 13 (“difficulty eating hard foods”), Question 14 (“choking”), and Question 15 (“dry mouth”) of the KCL. Receiver operating characteristic (ROC) curves were generated to assess the association between frailty and oral function scores. Multivariate logistic regression was used to analyze factors associated with oral function. Results: Among the 661 participants, 39.5% were frail. Frailty rates tended to increase with increasing oral function scores. The optimal cut-off score for oral function corresponding to frailty was 2 points, with a specificity of 89.2% and a sensitivity of 54.8%. Multivariate analysis identified age and Health Assessment Questionnaire-Disability Index (HAQ-DI) as significant factors associated with oral function decline (i.e., a total score of ≥2 for Questions 13-15 of the KCL). Conclusion: Frailty is strongly associated with oral function decline in RA patients. This finding highlights the importance of monitoring the oral function of RA patients, since it not only reflects physical function, but also serves as a potential marker of frailty. Targeted interventions to improve oral function may play a vital role in reducing frailty risk and enhancing the overall well-being of RA patients.